The Impact of Monetary Policy on the Industry Sector in Indonesia - Henny Medyawati; Muhamad Yunanto (Jurnal Ekonomi dan Studi Pembangunan, 2021)
Several studies show that there is a relationship between monetary policy and industrial sector output. The main objective of this research is to analyze the impact of monetary policy on the industrial sector. The appropriate model for time series data that is not stationary is the Vector Error Correction Model (VECM). This study involved quarterly data during 2010 to 2019 from Central Bank of Indonesia (BI) and Statistics Indonesia (BPS). The empirical results indicate that the industrial sector has a positive response to the shock of the BI interest rate variable. On the other hand, the industrial sector gave a negative response to shocks from the consumer price index variable and the BI interest rate. The results of the variance decomposition show that the largest percentage contribution is shown by the inflation variable as measured by the Consumer Price Index (CPI) and Foreign Direct Investment (FDI). Keywords: BI rate, Monetary policy, Industry sector, VECMJEL Classification E52, E58